Conservation of Chauburji, Lahore in Relation to Orange Line (Al-Qamar, 2022)
Lahore is known to be second largest city in Pakistan and is well-known for its historical sites. Developmental schemes implemented by the Punjab Government can affect the cultural ethics of historic sites. This research classifies the issues regarding conservation of the historic monument with the reference of orange line project and prepares a conservation proposal for the historic monument of Chauburji, following the historical evidence from Archaeology Department Punjab. After the complete observation of rapid transit train project, recommendations and proposals will be useful for forming a shield zone knowing to be the main issue for conservation. The study will help in protecting the rich history of the city.
Keywords: Historical evidence; orange line; Chauburji Lahore